Improving Learning Quality through Implementation of Merdeka Curriculum in Elementary Schools - Muashomah; Kusmiyanti, Sa’idah; Agustyarini, Yhasinta (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2023)
This study analyzes curriculum evaluation management in implementing the Merdeka Belajar program at Sekolah Penggerak SDNU Mutiara Insani Mojo Kediri. This research employs a qualitative approach with data collection techniques through observation, interviews, and documentation. The findings indicate that implementing the Kurikulum Merdeka at SDNU Mutiara Insani Mojo Kediri has been implemented effectively and under sound evaluation principles. Curriculum evaluation is conducted periodically, involving various stakeholders, and the results of these evaluations are used to improve and develop the curriculum continuously. These findings suggest that evaluation management has positively contributed to enhancing learning quality at the school.